(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2026)
This scientific article comprehensively examines the content, forms, and development prospects of nursing practice in the context of healthcare system digitalization. The rapid development of information and communication technologies significantly affects all stages of healthcare delivery, particularly nursing practice. The role of electronic medical records, medical information systems, telemedicine, remote monitoring, and digital platforms supporting clinical decision-making in nursing practice is thoroughly analyzed. The article scientifically substantiates the importance of digital healthcare technologies in ensuring patient safety, improving the quality of medical services, and optimizing nurses’ work processes. The research findings demonstrate that the development of nursing practice in a digital environment is a crucial factor in ensuring the sustainable and effective functioning of the healthcare system.